Bentuk dan fungsi Tale Haji dalam acara pelepasan jamaah haji di Desa Pondok Agung Kecamatan Pondok Tinggi Kota Sungai Penuh - Irwan Ficha Sanjaya; Budiwirman Budiwirman (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2019)
The aim of this article is to express and explain about the form and function of Tale Haji while conducting the extrication event of Haji pilgrims based on Pondok agung village pondok tinggi subdistrict Sungai Penuh custom. The form of the Tale Haji displayed at this time is the area of study in this study. In the presentation and function of the Tale Haji which is an important performance in the release of the pilgrims is the focus of this research. This research was conducted with a qualitative research approach, with descriptive methods. Data collected by observation techniques, literature study, interviews, and documentation. The results showed that the Tale Haji performance was still maintained by the people of Pondok Agung Village to release the departing pilgrims. Tale Haji is displayed by standing making the shaf sideways, holding hands and facing each other between prospective worshipers with family and other communities. The Tale Haji function expresses the feelings of the prospective pilgrims who will go to Mecca and the feelings of families who leave through the Tale Haji poetry that contains messages and prayers.